Analysis Of Workload Using Nasa-tlx Method To Determine The Number Of Operator In Ciganitri Pants Garment - Revina Hardiyanti; Budi Sulistyo; Christanto Triwibisono (eProceedings of Engineering, 2018)
Abstract Ciganitri Pants Garment is a home industry engaged in field jeans convection, the activity is to make several jeans for men of different types. In carrying out its activities the operator at Ciganitri Pants Garment gets a high customer demand and often does not fulfill it, making the operator's mental workload increase. So it is necessary to analyze how much mental workload is experienced and what factors that influence it. Therefore Ciganitri Pants Garment can determine the right steps to improve conditions. One of method that can be used to measure mental workloadn is NASA-TLX. The NASA-TLX method is a method of measuring mental workload that divides workload into 6 working element dimensions. From the results of NASA-TLX calculations, the value of mental workload for several operators Ciganitri Pants Garment is at a high level with the highest mental workload indicators are PD (Physical Demand) and MD (Mental Demand) scales. Therefore, it is necessary to add operators to 4 Work Stations, so that the operator, which originally 12, became 16 operators working on 10 Work Stations. Research of T.Fariz Hidayat, et al (2013) that conducted in one of the hospital in Indonesia showed that the results of workload measurement that dominant in physical needs (PD) factors affect the workload of nurses. The results obtained in Ciganitri Jeans Konveksi have in common with the results of research conducted in one of the hospital in Indonesia that physical needs are the most important factor that caused the high workload. Keyword: Workload, NASA-TLX, Pants Garment.